Effectiveness for quantity of product using forecasting method in clarents - Yuniar, Yura Armianty; Utama, Akbar Adhi (Journal of Innovation, Business and Entrepreneurship, 2019)
Basically, Forecasting is one of important things the running of a business. In addition, forecasting makes business continuity efficient. There are several factors that determine sales of our business. In the field of fashion trend is a considerable influence, but we still have to determine how many items are effective for us to produce until they run out. Clarents company is a company that sells cardholders, this company is categorized as Small Medium Enterprise. This company previously always used the Rule of Thumb system in its forecasting process. The problem that is always experienced by this company is the accumulation of unsold products. This causes the profit obtained is not in accordance with the specified target. Analysis using 3 months past demand was used to determine the forecasting method. It turns out the most suitable forecasting demand for 6 slot, 12 slot and 24 slot is Time Series Decomposition Multiplicative method, which the method has the lowest MAPE, MAD, MSD. And for the new method we can minimize of lost sale. For model 6 slot we can reduce of lost sale from 62 to 32, for model 12 slot from 124 to 74, and for the 24 method we can reduce of lost sale from 304 to 180. By using this method, we can prepare how many items we have to produce in the future. It can also increase the company's sales results.Keywords: Forecasting demand, Planning, Time Series Decomposition, Target Profit.